A General Method for Quantification and Discovery of Acyl Groups Attached to Acyl Carrier Proteins in Fatty Acid Metabolism Using LC-MS/MS. Issue 4 (14th February 2020) - Nam, Jeong-Won; Jenkins, Lauren M.; Li, Jia; Evans, Bradley S.; Jaworski, Jan G.; Allen, Doug K.
Abstract : Acyl-ACPs that enable fatty acid biosynthesis were uniquely profiled and quantified, resulting in discovery of novel ACP products with unknown function and providing a method for rigorous comparisons. Abstract: Acyl carrier proteins (ACPs) are the scaffolds for fatty acid biosynthesis in living systems, rendering them essential to a comprehensive understanding of lipid metabolism. However, accurate quantitative methods to assess individual acyl-ACPs do not exist. We developed a robust method to quantify acyl-ACPs to the picogram level. We successfully identified acyl-ACP elongation intermediates (3-hydroxyacyl-ACPs and 2, 3- trans -enoyl-ACPs) and unexpected medium-chain (C10:1, C14:1) and polyunsaturated long-chain (C16:3) acyl-ACPs, indicating both the sensitivity of the method and how current descriptions of lipid metabolism and ACP function are incomplete. Such ACPs are likely important to medium-chain lipid production for fuels and highlight poorly understood lipid remodeling events in the chloroplast. The approach is broadly applicable to type II fatty acid synthase systems found in plants and bacteria as well as mitochondria from mammals and fungi because it capitalizes on a highly conserved Asp-Ser-Leu-Asp amino acid sequence in ACPs to which acyl groups attach. Our method allows for sensitive quantification using liquid chromatography–tandem mass spectrometry with de novo–generated standards and an isotopic dilution strategy and will fill a gap in our understanding, providing insights through quantitative exploration of fatty acid biosynthesis processes for optimal biofuels, renewable feedstocks, and medical studies in health and disease.